Pharmacist Led Assessment of Drug Related Problems in Type 2 Diabetes Mellitus Patients - Zia Inamdar, Syed (International Journal of Psychosocial Rehabilitation, 2020)
Patients with Type-2 diabetes mellitus are known to be at risk of drug related problems as they receive multiple medications due to co-morbidities associated with the condition. A Drug related problem is defined as any event involving drug treatment that potentially interferes with the patient achieving an optimum outcome of medical care. Thisstudy tends to evaluate the prevalence of drug related problems and related factors among the study population. An interventional study in adults with Type 2 diabetes was conducted in a tertiary care hospital. The study subjects were reviewed to collect relevant data and analyzed to report the prevalence of drug related problems (DRPs) occurred during the management of diabetic patients. A total of 107 Study population were finally reviewed with a reporting incidence 278 DRP’s and were grouped under the following; drug without indication 25(8.99%), indication without drug 27(9.71%), drug not appropriate for therapy 12(4.32%), supra and sub therapeutic dose 03(1.08%), additive toxicity 03(1.08%), drug duplication 07(2.52%), adverse drug reaction 08(2.88%) drug interactions 193 (69.42%). Majority of the drug related problems were appropriately intervened. Age, polypharmacy, multiple co morbidities were the factors associated with DRP’s in diabetic patients. The study revealed a substantial incidence of drug related problems associated with drug therapy in management of diabetes.